HUBUNGAN FAKTOR-FAKTOR SOSIAL EKONOMI PETANI DENGAN TINGKAT PENERAPAN TEKNOLOGI PENGELOLAAN TANAMAN TERPADU (PTT) USAHATANI PADI SAWAH DI KABUPATEN KENDAL - Agustinawati Agustinawati; Marcelinus Mollo; Sutarto Sutarto (AGRITEXTS: Journal of Agricultural Extension, 2006)
ICR is the approachment of crop management with implementation some plantation technology component that gives whole effect. Compenen of ICR including: decided the comodity choice that is adaptive according to agroclimate and plant season, adaptive superior variety, and high quality seed; management methode of germ and disease, and right methode to handle harvest and afterward. The research is aimed to study the factors of farmer's social economic, the adoption level of farmers toward ICR programme and the relationship between the factors farmer's social economic with the adoption level farmer toward ICR programme in Kendal regency. The basic methode used in thes research is analytical descriptive with survey technique. The research place is determined intentionally (purposive) that are Cepiring subdistric at Kangkung subdistrict. The methode in taking sample is census, with number of sample are 100 respondent. The result of research show that majority respondent's adoption toward ICR programme classify to good enough. The result of compare means analize show that more young, more wide of field, more high of formal education, nonformal education, income and participation in farm-group the adoption of ICR are more better. A test of rank spearman correlation in 95% significant level show that there are significant correlation between the variable of formal education, nonformal education, income, wide of field and participation in farm-group, while age show that there is no significant correlation with adoption level of ICR programme.